Preventive effects of Polygonum minus essential oil on cisplatin-induced hepatotoxicity in sprague dawley rats - Norhashima Abd Rashid,; Farida Hussan,; Asmah Hamid,; Nurul Raudzah Adib Ridzuan,; Teoh, Seong Lin; Siti Balkis Budin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cisplatin is a chemotherapeutic agent widely used in treating various types of cancer. However, its usage is restricted due to the adverse hepatoxicity, as seen in approximately 36% of cancer patients receiving cisplatin treatment. Polygonum minus essential oil has high antioxidant capacity, and is enriched with terpenoids and phenolic compounds. The objective of this study was to investigate effects of P. minus essential oil (PmEO) supplementation on cisplatin-induced hepatotoxicity in rats. Male rats were divided into seven different groups, namely: control (C), cisplatin-induced (CP), positive control with β-caryophyllene 150 mg/kg (BCP), PmEO 100 mg/kg (PmEO100CP), PmEO 200 mg/kg (PmEO200CP), PmEO 400 mg/kg (PmEO400CP) and PmEO 400 mg/kg alone (PmEO400). PmEO and BCP was given orally for 14 days prior to a single dose cisplatin (10 mg/kg) injection on day 15 and rats were sacrificed on day 18. Liver enzymes, histology, ultrastructural morphology and oxidative stress markers such as glutathione, glutathione peroxidase, catalase, superoxide dismutase and malondialdehyde were assayed. Compared to controls, levels of transaminase enzymes, serum bilirubin and oxidative stress were all increased in CP, PmEO200CP and PmEO400CP groups. However, only PmEO100CP and BCP groups reduced these increases in level of transaminase enzymes and oxidative stress compared to CP group. On both light microscopic and ultrastructural examination, CP and PmEO400CP groups showed hepatotoxicity, exhibited by cytoplasmic vacuolation, congested blood sinusoids and increased number of Kupffer cells. However, these changes were minimized in the PmEO100CP group. Therefore, we concluded that PmEO given at 100 mg/kg has preventive effect against cisplatin-induced hepatotoxicity in rats.